2018
DOI: 10.1002/slct.201800697
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I)/Ag(I)‐3‐(2‐Pyridyl)‐5,6‐diphenyl‐1,2,4‐triazine‐p,p’‐disulfonate Based Coordination Polymers: Synthesis, Structures and Photoluminescent Properties

Abstract: Three new coordination polymers (CPs), namely [Cu2(pdtd)(bpy)2]n.12H2O (1), [Ag2(pdtd)(azpy)]n (2) and [Ag2(pdtd)]n (3) (where pdtd=3‐(2‐Pyridyl)‐5,6‐diphenyl‐1,2,4‐triazine‐p,p’‐disulfonate, bpy=4,4’‐bipyridine and azpy=4,4’‐azopyridine), have been synthesized and characterized using elemental analysis, IR, UV‐vis, thermal studies and finally their structures were determined by single crystal X‐ray diffraction technique. The single crystal structural studies reveal that CP 1 is one dimensional structure while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…The decrease in π-stacking distance for the material reported here is a result of the 'off-set' π-stacking arrangement, strengthening interactions, and currently represents the closest stacking observed for a tpt-containing framework. A disadvantage of such interpenetration is the closure or blockage of pore channels created by the original structure, as seen from Figure 2; when transforming the material from a 3D porous material to a 1D porous material along the a-axis (Figure 3a), with dimensions of 9 × 13 Å hosting water and tetrafluoroborate molecules, with one (BF 4 ) − per copper, there is a reduction in the Cu 2+ reactant during the reaction to Cu 1+ within the product formed (as observed during synthesis via color change, and confirmed via bond valence summation; such behavior has been observed in previous studies [15][16][17][18]). In contrast to the close tpt packing, the 2.67 Å Cu 1+ -(BF 4 ) − distance is much longer than typical Cu-F bond lengths (1.90-1.93 Å), suggesting that no formal bond exists, but merely an attractive stabilizing interaction between Cu 1+ and (BF 4 ) − , indicating anion exchange to a smaller anion, e.g., Cl − , and hence that open metal sites (OMS) may be possible.…”
Section: Resultssupporting
confidence: 76%
“…The decrease in π-stacking distance for the material reported here is a result of the 'off-set' π-stacking arrangement, strengthening interactions, and currently represents the closest stacking observed for a tpt-containing framework. A disadvantage of such interpenetration is the closure or blockage of pore channels created by the original structure, as seen from Figure 2; when transforming the material from a 3D porous material to a 1D porous material along the a-axis (Figure 3a), with dimensions of 9 × 13 Å hosting water and tetrafluoroborate molecules, with one (BF 4 ) − per copper, there is a reduction in the Cu 2+ reactant during the reaction to Cu 1+ within the product formed (as observed during synthesis via color change, and confirmed via bond valence summation; such behavior has been observed in previous studies [15][16][17][18]). In contrast to the close tpt packing, the 2.67 Å Cu 1+ -(BF 4 ) − distance is much longer than typical Cu-F bond lengths (1.90-1.93 Å), suggesting that no formal bond exists, but merely an attractive stabilizing interaction between Cu 1+ and (BF 4 ) − , indicating anion exchange to a smaller anion, e.g., Cl − , and hence that open metal sites (OMS) may be possible.…”
Section: Resultssupporting
confidence: 76%
“…Interestingly, the fluorescence intensities of compounds 2 and 4 have obviously increased compared with the free auxiliary ligand, which may be due to the coordination of metal clusters to the ligand, resulting in increased rigidity of the ligand and reduced nonradioactive loss (Mu et al, 2011;Li et al, 2012;Singh, 2018Singh, , 2019.…”
Section: Fluorescence Propertiesmentioning
confidence: 99%
“…They stand out among polymer materials owing to their properties, for instance, large surface area, adjustable structure and high porosity (Furukawa et al, 2010;Zhou et al, 2012;Long & Yaghi, 2009). Extensive efforts have been devoted to synthesizing and investigating novel MOFs, not only because of their intriguing structures and distinctive topologies, but also due to their promising applications as functional materials in many fields, such as luminescence (Cui et al, 2012a,b;Hu et al, 2014Hu et al, , 2020Liu & Dai, 2018;Yu et al, 2020;Singh, 2018Singh, , 2019Singh & Bhim, 2016), drug delivery and release (Chen et al, 2018a,b;Zheng et al, 2016;Pan et al, 2020), gas storage and separation (Li et al, 2009(Li et al, , 2017Lee et al, 2009;Gong et al, 2009;Taylor et al, 2018), catalysis (Parmar et al, 2018;He et al, 2018;Wu et al, 2019;Pan et al, 2019;Singh & Bharadwaj, 2013), supercapacitors (Liu et al, 2020) and magnetism (Cheng et al, 2010;Tian et al, 2015;Xu et al, 2003). As is well known, the construction of stable coordination frameworks is mainly dependent on a combination of several factors, such as the organic ligand, solvent, metal centre, pH value, temperature, and so on (Mu et al, 2012;Sun et al, 2013;Bu et al, 2002;Liu et al, 2007;Zhang et al, 2009;Manna et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among the three Ag-N bond lengths formed by each PPTA ligand, the Ag1-N2 and Ag1-N3 bonds (both N atoms belong to the triazine ring) are the longest and shortest, respectively. A study of the literature revealed that there are six examples of coordination of 3-(pyridin-2-yl)-1,2,4-triazinebased ligands to an Ag atom (Safin et al, 2016;Aneheim et al, 2013;Marandi et al, 2011;Singh, 2018), in which the Ag atom has a coordination number of 3-5 and none of them has square-planar geometry. The coordination mode of the triazine ligands in four examples are similar to 2, which means that this ligand selectively chooses this mode in binding to Ag atoms.…”
Section: Figurementioning
confidence: 99%